Symposium - Promising Practices in Scholar-Union Collaboration: Lessons for Building Effective Research Partnerships - Armstrong, Pat; Bittman, Kevin; Hurley, Michael; Stanford, Jim; Tucker, Sean; Vela, Jakin; Weststar, Johanna; Wilson, Fred (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2025)
This symposium considers the prospects for research collaboration between industrial relations scholars and trade unions, as well as its challenges. First, in remarks presented in the 2025 H.D. Woods Lecture at the Canadian Industrial Relations Association / Association canadienne des relations industrielles conference, Jim Stanford reviews the mutual benefits for both scholars and trade unionists from successful research partnerships and proposes strategies for building more respectful and trusting relationships between them. The symposium then presents three case studies of lasting, productive research partnerships, each described by a matched pairing of a scholar with a union representative. Lessons are drawn for future research collaborations.